MİDE ADENOKARSİNOMLU BİR HASTADA AKANTOZİS NİGRİKANS - AKÇA, Özlem; DAVRAN, Ebru; BACA, Bilgi; ÇOLAK, Asuman; ERGÜNEY, Sabri; ALVER, Olcay (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Acanthosis nigricans is classified into benign and malignant forms on the basis of clinical associations. Most importantly, it often precedes the diagnosis of a new or recurrent tumor. Malignant acanthosis nigricans (MAN) is most commonly associated with intra-abdominal malignancies. We describe a case of MAN which was the first sign of gastric adenocarsinoma.